Game Running Performance and Fitness in Women's Futsal - Palucci Vieira, Luiz Henrique [UNESP]; Arins, Francimara Budal; Guglielmo, Luiz Guilherme Antonacci; De Lucas, Ricardo Dantas; Carminatti, Lorival José; Santiago, Paulo Roberto Pereira (Thieme, 2021)
The study aimed to verify possible associations between game-play running performance and outcomes derived from fitness (running) tests in female futsal players. Sixteen women professional elite futsal players from a 1 stdivision league team (19.2±2 years-old, 4.3±2.1 years of experience) participated. Firstly, a graded incremental treadmill test was adopted to determine maximal oxygen uptake (VO 2max). Following 72 h of laboratory protocol, players were asked to perform a repeated-sprint test on a court (8×40 m with two 180° change-of-directions). Twenty-four hours after, players participated in a one-off friendly game (two 20-min half-times). A computerized automatic image recognition software (DVIDEOW; 30 Hz) allowed to determine game running performance variables. Fatigue index and best time in the court test and VO 2maxand its attached speed derived from laboratory-based test showed significant moderate-to-moderately high correlations (r=- 0.59-0.76; p<0.05) with some game running performance outputs, notably related to high-intensity running. In conclusion, the present study provided initial evidence on associations between two fitness tests and one-off game running performance in female futsal. Information derived from the work potentially help conditioning professionals working with female futsal athletes gain awareness about some properties of common testing tools.
Keywords: automatic tracking; fitness assessment; high-intensity running; physical capacity; team sports